Multiphysics Modeling Investigation of Casing Storage, Wellbore Transport, and Formation Heterogeneity Effects on Groundwater Sampling - Yu He; Yuzheng Liu; Minjae Kim; Haiying Huang; Chunhui Lu; Deyi Hou; Jian Luo (Water Resources Research)
Abstract Groundwater sampling is critical for hydrogeological investigations and accurate hydrogeochemical analyses, influenced by two key processes within the well: depletion of casing storage and completion of wellbore transport. This study characterizes their combined effects on purging efficiency in groundwater sampling across various chemical and hydrogeological settings. A coupled multiphysics flow and transport model is developed, accounting for transient laminar flow and solute transport within the wellbore, and Darcy flow in the aquifer. Results indicate that sufficient well purge is constrained by the process with the longer characteristic time scale. In high‐yield aquifers, purging until water level stabilizes or purging 3 to 5 well screen volumes is inadequate for representative samples, as wellbore transport is the limiting process. Thus, multiple successive readings of water quality indicators or contaminant concentrations over an extended period are required. In low‐yield aquifers, the casing storage effect is significant, and drawdown stabilization suggests a sufficient well purge. However, purging time and wastewater volume tend to be excessive. The “High‐Stress Low‐Flow” (HSLF) strategy can reduce purging time and establish a predictable sampling window. A modified analytical solution, assuming complete mixing in the wellbore, provides an accurate approximation of the multiphysics model for both homogeneous and stratified formations. In heterogeneous aquifers, high variance of mass inflow at the screen leads to a lower degree of mixing within the screen. However, stabilized sample concentrations at the intake consistently reflect a weighted average of the total mass inflow, regardless of intake placement or formation stratification.